For Better, For Worse - Lambert, Carolyn. (Milton)
1 online resource (226 pages)
Keywords: "This interdisciplinary volume explores the fictional portrayal of marriage by women novelists between 1800 and 1900. It investigates the ways in which these novelists used the cultural form of the novel to engage with and contribute to the wider debates of the period around the fundamental cultural and social building block of marriage. The collection provides an important contribution to the emerging scholarly interest in nineteenth-century marriage, gender studies, and domesticity, opening up new possibilities for uncovering submerged, marginalized, and alternative stories in Victorian literature. An initial chapter outlines the public discourses around marriage in the nineteenth century, the legal reforms that were achieved as a result of public pressure, and the ways in which these laws and economic concerns impacted on the marital relationship. It beds the collection down in current critical thinking and draws on life writing, journalism, and conduct books to widen our understanding of how women responded to the ideological and cultural construct of marriage. Further chapters examine a range of texts by lesser-known writers as well as canonical authors structured around a timeline of the major legal reforms that impacted on marriage. This structure provides a clear framework for the collection, locating it firmly within contemporary debate and foregrounding female voices. An afterword reflects back on the topic of marriage in the nineteenth- century and considers how the activism of the period influenced and shaped reform post-1900. This volume will make an important contribution to scholarship on Victorian Literature, Gender Studies, Cultural Studies, and the Nineteenth Century."--Provided by publisher.